IMPLEMENTASI UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERKAWINAN (STUDI TERHADAP PENCEGAHAN PERNIKAHAN DINI DI DESA WONGSOREJO, KECAMATAN WONGSOREJO, KABUPATEN BANYUWANGI) - Ramadhani Tahta Fahreza; Sri Wilujeng; Safrieta Jatu Permatasari (Bajang Institute, 2024)
Marriage is a bond between a man and a woman as husband and wife with the aim of forming a happy and lasting family (household) until death separates. While early marriage is a marriage event carried out by children under 16 years old for women and under 19 years old for men. Law Number 16 of 2019 concerning marriage explains that the minimum age limit for men is 19 years old while for women it is 16 years old. As happened in Wongsorejo Village, the rate of early marriage always rises due to several factors behind it, including: economic factors and matchmaking cultural factors. The research method used in this study is qualitative research and is a type of descriptive research. Implementation is focused on the ideas of George C. Edward III in Agustino (2016:136-141) 1) Communication, 2) Resources, 3) Disposition, and 4) Bureaucratic Structure. Research results: First, communication, socialization of early marriage prevention in Wongsorejo Village. Second, Resources, the number of employees is limited. So that there is collaboration between the government and the community. Third, disposition, the village staff showed good performance in carrying out their duties and had high dedication. Fourth, Bureaucratic Structure, each level and section in the organizational structure has clear duties and responsibilities with work SOP